Xenopus Resources: Transgenic, Inbred and Mutant Animals, Training Opportunities, and Web-Based Support - Horb, Marko; Wlizla, Marcin; Abu-Daya, Anita; McNamara, Sean; Gajdasik, Dominika; Igawa, Takeshi; Suzuki, Atsushi; Ogino, Hajime; Noble, Anna; , Centre de Ressource Biologique Xenope team in France; Robert, Jacques; James-Zorn, Christina; et al. (Frontiers in Physiology, 2019)
Two species of the clawed frog family, Xenopus laevis and X. tropicalis, are widely used as tools to investigate both normal and disease-state biochemistry, genetics, cell biology, and developmental biology. To support both frog specialist and non-specialist scientists needing access to these models for their research, a number of centralized resources exist around the world. These include centers that hold live and frozen stocks of transgenic, inbred and mutant animals and centers that hold molecular resources. This infrastructure is supported by a model organism database. Here, we describe much of this infrastructure and encourage the community to make the best use of it and to guide the resource centers in developing new lines and libraries.